A Linguistic Study of Epitaphs in Selected English Texts (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims at analysing epitaphs written by Thomas Moore for the memory of Rupert Southey, the epitaph is analysed linguistically and stylistically on four levels graphology, phonology, morphology, and lexico-syntax level to explore the elements that the writer uses the most at each level. Bearing in mind Nowottny approach (1962) (to text analysis) who believes that the linguistic analysis of a literary text is not just a marginal but a necessity” (Bakuuro etal., 2018:34). The researcher has selected and analysed a written epitaph of famous individual associated with English, literature. The study involves both literary and linguistic analysis, with much more concentration through the analysis on the aspect of linguistics. In fact, in order for stylistic analysis of literary texts to be good it needs to in volve linguistic analysis and this for the purpose of making the analysis standard and is targeted to unveil the author’s ‘full style’. Based on the results of data analysis, certain remarkable points have arisen. The most important result that has been achieved is that on the level of Graphology, the poet mostly used the punctuation Marks, while the most used device on the phonological level was the rhyme. Furthermore, the findings show that on the morphological level the writer mainly used suffixes.While on the levels of lexicosyntax and parts of the speech, anastrophe and prepositions were mainly used.